Prevalence of some intestinal parasitic protozoa causing diarrhea among children in Sebha city, Libya - Alshref فاطمة; Ibrahim حسن (Journal of Pure & Applied Sciences, 2022)
This study was conducted on the prevalence of two types of intestinal protozoan parasites causing diarrhea, Entamoeba histolytica and Giardia lamblia, among children in Sebha. During this study, 262 stool samples were collected (138 boys and 124 girls), ranging in age from one month to 14 years, from September 2019 to February 2020. Data were recorded for each child of sex, age, and place of residence. All samples were examined by the direct method and the concentration of formalin and ether. The results of the study indicated that the prevalence of total infection with these two parasites was 6.5% (3.4% for Entamoeba histolytica/dispar, 3.1% for Giardia lamblia), with no significant difference between them in the prevalence of infection (p=0.572). The study also showed that the infection rate for girls was 7.3%, which is higher than 5.8% for boys, with no significant difference between them (p=0.409). The highest prevalence was 8.1% in the age group 5-9 years, with no statistical differences between the different age groups. The results also revealed a significant difference (p = 0.001) in the prevalence of infection between the direct (4.2%) and the concentration methods (6.5%). Depending on the place of residence, the results indicated that the highest rate of infection was in the Hajarah area, at 25%. This study aims to determine the prevalence of two intestinal protozoan parasites that cause diarrhea in children in Sebha, namely Entamoeba histolytica and Giardia lamblia.